Enigma - Harris, Robert, 1957- (Ivy Books, 1996)
England 1943. Much of the infamous Nazi Enigma code has been cracked. But Shark, the impenetrable cipher used by Nazi U-boats, has maked the Germans' movements, allowing them to destroy Allied vessels. Now a top-secret team of British cryptographers works feverishly around the clock to break Shark. And when brilliant mathematician Tom Jericho succeeds, it is the stuff of legend.